Akuntan dan Akuntansi Dalam Peran Cipta Realitas Sosial dengan Nilai-Nilai Etika - Nursanty, Ida Ayu Nursanty; Endang Kartini; Yusi Faizatul Octavia; Baiq Desthania Prathama (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to examine accountants and accounting in the role of creating social reality with ethical values. This research uses a spiritualist-rationalist paradigm. The researcher highlights that when the social reality that is created is a social reality that is dry with ethical values, then this kind of social reality will have a big influence in shaping individual behavior to behave the same as the